The interplay between product innovation, publishing, patenting and developing standards - Knut Blind; Bastian Krieger; Maikel Pellens (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Firms use a variety of practices to disclose the knowledge generated by their R&D activities, including, but not limited to, publishing findings in scientific journals, patenting new technologies, and contributing to developing standards. While the individual effects of engaging in the listed practices on firm innovation are well-understood, the existing literature has not considered their interrelation. Therefore, our study examines if the three practices are complements, substitutes, or unrelated in terms of firms' performance with product innovations new to the market. Our analysis builds on a sample of innovation-active firms from the German Community Innovation Survey, which includes information on the development of standards, enhanced with information on firms' engagement in patenting and publishing. We find that 26% of innovation-active firms engage in at least one of the three practices, and 22% of engaging firms combine them. Using supermodularity tests, we show that publishing and patenting as well as patenting and developing standards are substitutes. Publishing and developing standards are not significantly linked. Based on our findings, we derive implications for innovation management and policy.
Keywords: O31; O32; O34; 330; Standardization; patents; scientific publications; product innovation